METODE DRILL AUDITORI TAKTIL TERHADAP KEMAMPUAN MELAFALKAN HURUF-HURUF AL-QURAN SISWA TUNANETRA KELAS VII SMPLB-A - SHOFI ISA ANSHORI, M. (Jurnal Pendidikan Khusus, 2016)
Abstract Blind students of class VII in SMPLB-A YPAB Gebang Putih Surabaya had difficulty in pronouncing Hijaiyah alphabets or fluency in reading Al-Quran. The blind students required innovative and creative learning method which was suitable with the students’ condition and needs. The appropriateness method was based on the principles and the teaching pattern of blind students. The purpose of this research was to describe the influence of tactile auditory drill method. This method had been modified based on the principles and the teaching pattern of blind students in enhancing pronouncing Al-Quran alphabets ability to blind students of class VII in SMPLB-A YPAB Gebang Putih Surabaya. The research method used was quantitative with Pre-Experiment arrangement with One Group Pretest-Posttest design. The data was collected using test technique and documentation. The technique of data analysis used was using Sign Test formula. The research result indicated the average value of pretest was 136 and posttest was 192,5. The result of data analysis indicated that Zh value = 2,05 and Zt with n = 6 and  α = 5% was 1,96, so the interpretation was that Zh was greater than Zt. It could be concluded that Ho was refused and Ha was accepted, it meant that there was influence of drill tactile auditory method toward the ability of pronouncing Al-Quran alphabets to blind students of class VII in SMPLB-A YPAB Gebang Putih Surabaya.   Keywords: Drill method, pronouncing Al-Quran alphabets